2019
DOI: 10.1002/jmri.26710
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional turbo‐spin‐echo amide proton transfer‐weighted mri for cervical cancer: A preliminary study

Abstract: Background Amide proton transfer‐weighted (APTw) imaging has shown great potential in the diagnosis of cancer, but has yet not been well studied in cervical cancer. Purpose To evaluate the image quality and clinical feasibility of APTw MRI for cervical cancer. Study Type Prospective. Population In all, 75 patients with cervical lesions and 49 healthy volunteers. Field Strength/Sequence 3.0 T, 3D turbo spin echo (TSE) APTw sequence. Assessment Three radiologists, blinded to the clinical data, independently eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 34 publications
(75 reference statements)
3
17
0
1
Order By: Relevance
“…5 To date, multiple novel magnetic resonance imaging (MRI) techniques, such as diffusion-weighted imaging (DWI) based on monoexponential and nonmonoexponential models, dynamic contrast-enhanced (DCE) quantitative analysis, blood oxygenation level-dependent (BOLD), and amide proton transfer-weighted (APTw) MRI have been applied to analyze the pathological features of CC. [6][7][8][9] However, except for DWI based on the monoexponential model, all these techniques face issues of excessive scanning duration, complicated image postprocessing, or low reproducibility. These factors restrict their wide application in clinical practice.…”
mentioning
confidence: 99%
“…5 To date, multiple novel magnetic resonance imaging (MRI) techniques, such as diffusion-weighted imaging (DWI) based on monoexponential and nonmonoexponential models, dynamic contrast-enhanced (DCE) quantitative analysis, blood oxygenation level-dependent (BOLD), and amide proton transfer-weighted (APTw) MRI have been applied to analyze the pathological features of CC. [6][7][8][9] However, except for DWI based on the monoexponential model, all these techniques face issues of excessive scanning duration, complicated image postprocessing, or low reproducibility. These factors restrict their wide application in clinical practice.…”
mentioning
confidence: 99%
“…The main challenge for APT imaging is B0 field inhomogeneity (20). Ideally, the APT calculation only needs to acquire images with saturation RF applied at ±3.5 ppm.…”
Section: A Cmentioning
confidence: 99%
“…Investigators in recent human studies have also reported preliminary APT findings in the breast (16)(17)(18)(19), cervices (20,21), prostate (22,23), and chest (8), demonstrating that it is an effective tool for tumor detection and characterization. APT values were higher in cancers than in normal surrounding tissues (22) and benign tumors (8).…”
Section: Introductionmentioning
confidence: 95%
“…; 利用表观弥散系数(apparent diffusion coefficient, ADC)定量特征, 实现术前对宫颈癌转移淋巴结 的精准检出和分期评估, 成功预测宫颈癌病理类型及 分化程度, 辅助临床治疗方案制定 [46] . 在国际上率先 开展了全球最大样本量的女性生殖系统酰胺质子转移 加权(amide proton transfer weighted, APTw)成像研究, 探索了国际新兴APTw成像技术在宫颈癌、子宫内膜 癌、子宫腺肌症中的应用价值 [47] .…”
Section: 针对肝脏灌注Ct成像 我科评价了灌注参数的正unclassified